A case report on ultrasound-guided pericardiocentesis with a right parasternal approach: a novel in-plane lateral-to-medial technique - Najem Abdullah Mohammed; Tanweer A. Al-zubairi; Moad H. Al-soumai (International Journal of Emergency Medicine, 2024)
Abstract Introduction Emergency pericardiocentesis is a life-saving procedure that is performed to aspirate fluid from the pericardial space in patients who have severe pericardial effusion that is causing hemodynamic compromise. The current gold standard for pericardial fluid aspiration is ultrasound-guided pericardiocentesis. Echocardiography with a low-frequency transducer has generally been used in pericardiocentesis, but this method lacks real-time visualization of the needle trajectory, leading to complications. Therefore, we describe a case involving an ultrasound-guided pericardiocentesis method using a novel in-plane technique with a lateral-to-medial approach via the right parasternal and a high-frequency probe. The method was performed for an infant with cardiac tamponade. Case presentation We present a case of a 14-month-old male infant who was brought to the emergency room with a history of cough, shortness of breath, and fever following recurrent chest infections. Despite prior treatments, his condition deteriorated, and signs of cardiac tamponade were evident upon examination. Cardiopulmonary point-of-care ultrasound confirmed the presence of a large pericardial effusion with tamponade. Emergency pericardiocentesis was performed using the novel in-plane technique, resulting in successful fluid aspiration and stabilization of the patient’s condition. Technique description The proposed technique involves positioning a high-frequency ultrasound probe over the right parasternal area to obtain real-time visualization of the needle trajectory and surrounding structures, including the sternum, right internal thoracic vessels, pleural sliding end point, pericardial effusion, and myocardium. The needle is inserted laterally to medially at a 45-degree angle, ensuring safe passage between the pleural sliding endpoint and the right internal thoracic vessels while reaching the pericardial effusion. Conclusion The presented technique provides real-time visualization of the needle and surrounding structures, which may potentially help to avoid complications and improve accuracy. The proposed technique may potentially enable access for emergency pericardiocentesis and for loculated pericardial effusion that has formed around the right atrium. Nevertheless, further studies with large patient populations are needed.